Carbon and curriculum : towards evidence-based climate change education in Canada - Wynes, Christopher Seth (2015)
Despite an overwhelming scientific consensus that climate change is a threat to our society, many young Canadians do not view it as a major issue. This suggests flaws in the way that youth are educated on climate change. I therefore investigated climate change education in Canada to recommend improvements. I analyzed Canadian secondary science curricula according to two frameworks to determine how thoroughly climate change is addressed. Results showed that Canadian provinces provide more comprehensive coverage of climate change than American states (70% of Canadian provinces give the highest level of coverage compared to 10% of American states). In general, learning objectives in Canadian provinces tend to focus on knowledge of climate change with little or no emphasis on scientific certainty or ways to address the issue. These results led me to conduct interviews with six individuals responsible for curriculum design in different provinces to see how documents are developed and whether political controversies influence the writing process. Interviewees described a development process relying on input from professionals, institutions and members of the public that is free of political interference. In some cases, efforts to remain neutral on this controversial subject may have led to descriptions of social controversy where there is actually scientific consensus on climate change. Following a review of current literature, I evaluated a list of potential behaviours to find the most effective ways to reduce an individual’s carbon footprint. The four high-impact actions I identified were: have fewer children, avoid air travel, live car free, and eat a plant-based diet. I then analyzed ten Canadian science textbooks to see which types of personal behaviours are currently recommended to students for reducing their carbon footprint. Textbooks encouraged low- or medium-impact behaviours such as recycling and household energy conservation, but rarely or never mentioned high-impact actions. While avoiding air travel can be 15 times more effective than recycling, it was mentioned one-fifth as frequently. This is problematic given the difficulty of meeting the 3.3 tonnes per capita reduction required by Canada’s current CO2 emissions target using low-impact actions. I suggest that if Canadian students are to be prepared for climate change, they should receive educational content that is consistent with evidence and delivered in the most effective ways. In line with this evidence-based approach, I prepared high school teaching materials that encourage the adoption of high-impact actions, using strategies suggested by studies of environmentally motivated behaviours.
Keywords: C:Canada; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change education; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; oa:topic:T12503 Social Acceptance of Renewable Energy Innovation; openalex:import; openalex:yes; ⛔ No DOI found